Merkel-cell polyomavirus (MCPyV) is rarely associated to B-chronic lymphocytic leukemia (1 out of 50) samples and occurs late in the natural history of the disease. - Comar, Manola; Cuneo, Antonio; Maestri, Iva; Melloni, Elisabetta; Pozzato, Gabriele; Soffritti, Olga; Secchiero, Paola; Zauli, Giorgio (J Clin Virol, 2012)
BACKGROUND: Previous studies have reported conflicting results on the frequency and potential pathogenetic role of Merkel-cell polyomavirus (MCPyV) in B-chronic lymphocytic leukemia (B-CLL). OBJECTIVES: To evaluate the association of MCPyV to B-CLL and to investigate the occurrence of MCPyV infection in relationship to the natural history of B-CLL. STUDY DESIGN: Samples of primary B-CLL peripheral blood mononuclear cells were obtained from two distinct University Hospitals of Italy from January 2010. For one B-CLL patient, it was possible to retrospectively examine the blood sample at diagnosis of B-CLL (March 2004) and several pathological tissues of cutaneous tumors occurring during the course of the disease. RESULTS: Only one out of 50 B-CLL blood samples examined was positive for MCPyV DNA. Retrospective analysis revealed that MCPyV DNA was absent in peripheral blood sample at diagnosis, becoming present only in advanced disease stages also in tonsil tissue as well as in a biopsy of differentiated squamous cell carcinoma. CONCLUSIONS: The association with MCPyV seems to represent a rare and late event during the natural history of B-CLL.
Keywords: Aged; Aged, 80 and over; Blood; Female; Humans; Italy; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Merkel cell polyomavirus; Middle Aged; Palatine Tonsil; Polyomavirus Infections; Prevalence; Skin; Tumor Virus Infections